2019
DOI: 10.1080/02673843.2019.1674165
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on Internet addiction among Moroccan high school students, its prevalence and association with poor scholastic performance

Abstract: There is a growing interest in research on the potential effects of Internet addiction [IA] on students' scholastic lives. Given that there is no research on this subject in Morocco, this cross-sectional study fills the gap by examining the prevalence of Internet Addiction among Moroccan high school students and its possible association with scholastic performance and other socio-demographic factors. Self-administered questionnaires were distributed to 305 students, consisting of sociodemographic questions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 58 publications
0
17
0
1
Order By: Relevance
“…(13) Comparing prevalence of IA is difficult due to the heterogeneity of assessment instruments, using varying samples and designs in the conducted studies and varying target populations. Furthermore, variation in the prevalence of IA is a known phenomenon as previous literature reported much variability in IA (15.8% of Moraccon high school students (26) , 35.6% of Indian teenagers (27) , 22.2% of teenagers in Iran (28) and 20% of the studied teenager in Japan (29) were Internet addicts ) and may be attributed also to variations in the accessibility of the Internet in different countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(13) Comparing prevalence of IA is difficult due to the heterogeneity of assessment instruments, using varying samples and designs in the conducted studies and varying target populations. Furthermore, variation in the prevalence of IA is a known phenomenon as previous literature reported much variability in IA (15.8% of Moraccon high school students (26) , 35.6% of Indian teenagers (27) , 22.2% of teenagers in Iran (28) and 20% of the studied teenager in Japan (29) were Internet addicts ) and may be attributed also to variations in the accessibility of the Internet in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…(9) However, the prevalence of IA in Arab countries is much higher, in Egypt in 2013, 2.6% of the studied high school students were Problematic Internet Users (PIUs) and 18.2% were Potential (PIUs) (10) , a much recent study (2019) demonstrated that the prevalence of IA among A Original Article adolescents in Egypt was 65.6%, while Facebook addiction prevalence was 92.8%. (2) In Arab countries, 15.8% of Moroccan adolescents (11) , and 5.3% of high school students in Saudia were Internet addicts (12) , while the prevalence of moderate to severe IA in Jordan reached 65% of the Jordan adolescents. (13) A large body of literature tried to explain risk factors of IA in the context of intrapersonal and interpersonal perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of physical inactivity and leisure-time sedentary behaviour in this study were similar to the global prevalence (85% physical inactivity and 30% sedentary behaviour), 26 higher than in a previous local study in Morocco, 9 and did not change over time. An increased use of mobile devices and the internet among adolescents 27 , 28 may have contributed to the continued high prevalence of sedentary behaviour in Morocco. However, the prevalence of walking or biking to school significantly increased in this survey from 2006 to 2010 and 2016, to almost 70% on any day of the week or 53.0% on 3–7 days a week, which is higher than the average in 27 Asia-Pacific countries (42.1%; ≥3 days/week).…”
Section: Discussionmentioning
confidence: 99%
“…The accessibility of such facilities in developing countries has put adolescents at risk of internet addiction [ 5 7 ]. Internet addiction among adolescents have been reported to be associated with poor outcomes including poor mental [ 8 , 9 ] and physical [ 10 , 11 ] health, substance abuse [ 12 ], academic difficulties [ 13 ], social isolation [ 14 ], self-injurious behavior and suicidal tendencies [ 15 17 ] and low self-esteem [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%